2011
DOI: 10.5536/kjps.2011.38.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Gene Responsible for Chicken Muscular Dystrophy

Abstract: By a series of positional cloning, we successfully narrowed down the AM candidate region to approximately 1.2 Mbp on GGA2q including 7 functional genes. Subsequently, we identified WWP1 gene as the most likely AM candidate by sequence comparison. The amino acid sequence around the candidate mutation was highly conserved among tetrapods, suggesting that WWP1 is the causative gene of chicken muscular dystrophy. Transfection of mutated WWP1 gene into C2C12 myoblasts disrupted muscle differentiation process. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The sequence comparison and analysis of seven genes in normal and dystrophic chickens revealed that the WWP1 missense mutation was predicted to influence the function of the WWP1 protein. The WWP1 missense mutation was not found in 111 normal birds from 16 strains and highly conserved among tetrapods [ 21 , 59 ].…”
Section: Genetic Linkage Analysis Of Am Genementioning
confidence: 99%
“…The sequence comparison and analysis of seven genes in normal and dystrophic chickens revealed that the WWP1 missense mutation was predicted to influence the function of the WWP1 protein. The WWP1 missense mutation was not found in 111 normal birds from 16 strains and highly conserved among tetrapods [ 21 , 59 ].…”
Section: Genetic Linkage Analysis Of Am Genementioning
confidence: 99%
“…Livestock species have been widely used for the biomedical researches, especially for chickens and pigs ( Matsumoto et al, 2011 ; Robb et al, 2011 ; Luo et al, 2012 ). Xenotransplantation using porcine cells, tissues and organs has focused on biomedical aspects, with the aim of decreasing wait times for patients who require an allotransplantation.…”
Section: Introductionmentioning
confidence: 99%